The effectiveness of the mixture of basil and betel leaves methanol extracts to suppress Colletotrichum acutatum, the causal agent of anthracnose disease on postharvest cayenne chili - CEPPY NASAHI; SUCI RAMADHANTY; SUDARJAT SUDARJAT; DENNY KURNIADIE; ICHSAN NURUL BARI; SYIFA NABILAH SUBAKTI-PUTRI (Society for Indonesian Biodiversity, 2023)
Abstract. Nasahi C, Ramadhanty S, Sudarjat S, Kurniadie D, Bari IN, Subakti-Putri SN. 2023. The effectiveness of the mixture of basil and betel leaves methanol extracts to suppress Colletotrichum acutatum, the causal agent of anthracnose disease on postharvest cayenne chili. Biodiversitas 24: 5513-5522. Anthracnose, caused by Colletotrichum acutatum, is a major disease in the cultivation of chili plantations in Indonesia. It is usually controlled by farmers using synthetic fungicides with many adverse effects. Therefore, botanical fungicides are applied as alternative control techniques. This research aimed to examine the effect of mixed methanol extract of basil (Ocimum basilicum) and betel leaves (Piper betle) against C. acutatum on cayenne chili (Capsicum annuum). The method used was a randomized block design (RBD) with thirteen treatments and three replications. The results showed that combining basil and betel leaf methanol extracts suppressed C. acutatum. Furthermore, the most effective treatment was a mixture of 1.5% of each of the extracts, which suppressed the development of the disease at 62.07%. The GC-MS profiling of the basil and betel leaf methanol fraction indicated the presence of bioactive compounds that have antifungal effects against anthracnose.